انتشار نقص التمعدن الرحوي القاطعي وعلاقته بالنخور عند أطفال مدينة دمشق بعمر 8- 10 سنوات. - نوايا فهميه (Latakia University Journal -Medical Sciences Series, 2016)
الخلفية والهدف: يتفاوت انتشار نقص التمعدن حول العالم بدرجة واضحة، ولا توجد دراسات حول انتشاره في مدينة دمشق. تهدف هذه الدراسة إلى تحري نسبة انتشار نقص التمعدن الرحوي القاطعي (MIH) وعلاقته بالنخور عند أطفال مدينة دمشق بعمر 8- 10 سنوات. مواد وطرائق البحث: ضمت الدراسة 1843 طفلاً (975 أنثى، 878 ذكر) بعمر وسطي 0.42±8.90 من الصفين الثالث والرابع من 17 مدرسة حكومية ابتدائية في مدينة دمشق، سورية. أجري الفحص السني للأطفال من قبل فاحص واحد (الباحث). تم تسجيل نقص تمعدن القواطع والأرحاء اعتماداً على معايير الاتحاد الأوروبي لطب أسنان الأطفال (EAPD). كما تم تقييم تأثير MIH على الأسنان باستخدام مشعرDMFT (الأسنان المرممة والمفقودة والمنخورة). تم استخدام اختبار Kolmogorov-Smirnov لدراسة توزع البيانات، واختباري T للعينات المستقلة وكاي مربع للمقارنة بين مجموعات الدراسة. تم الحكم على النتائج عند P ≤ 0.05. النتائج: بلغ عدد الأطفال المصابين بنقص التمعدن الرحوي القاطعي MIH 217 طفلاً من العدد الإجمالي للأطفال المشاركين في الدراسة وهو 1843 (%11.77). لم توجد فروق جوهرية بين الذكور والإناث في نسبة الإصابة بـ MIH (P=0.378). كانت البقع الخفيفة ذات الحدود الواضحة أكثر العيوب المينائية انتشاراً. كانت قيمة DMFT أعلى عند الأطفال المصابين بـMIH بالمقارنة مع قيمتها عند الأطفال غير المصابين. الاستنتاجات: بلغت نسبة انتشار نقص التمعدن الرحوي القاطعي عند أطفال مدينة دمشق %11.77. تبين نتائج الدراسة الحالية وجود ارتباط إيجابي بين MIH وبين وجود النخور السنية، وتشير إلى ضرورة تطبيق الإجراءات الوقائية في الأعمار المبكرة عند الأطفال المصابين. Background and Aim: The prevalence of hypomineralization varies considerably around the world. However, no prevalence data relating to hypomineralization exist for Damascus city. The aim of this study was to investigate the prevalence of Molar Incisor Hypomineralization (MIH) and its relationship with caries among the 8-10 year old children of Damascus city. Methods: The study was comprised of a total of 1843 children in Grade 3-4 (975 girls, 878 boys) (median age: 8.90±0.42) from 17 elementary public schools in Damascus, Syria. Subjects were evaluated clinically by one examiner (the researcher). Hypomineralized molars and incisors were recorded based on the European Association of Pediatric Dentistry (EAPD) criteria. The dental impact caused by MIH was evaluated with the Decayed, Missing and Filled Teeth (DMFT) index. Kolmogorov-Smirnov test was used for studying data distribution. Two-sample t-test and Chi-squared test were used for comparison between the groups. Significance was set at a P ≤ 0.05. Results: MIH was observed in 217 of the 1843 children (11.77%). We found no significant difference in the number of girls and boys with MIH (P=0.378). Mild demarcated opacities were the most frequent enamel defect. The mean value of DMFT in MIH children was greater than in unaffected children. Conclusions: The prevalence of MIH among children of Damascus city was 11.77%. The results showed a positive association between MIH and the presence of dental caries. These results indicate that preventive approaches of affected children are very important at an early developmental age.